EFEKTIVITAS DAN EFESIENSI MANAJEMEN KEUANGAN PADA BADAN USAHA MILIK DESA (BUMDES) DI DESA LUBUK LAWAS KECAMATAN BATANG ASAM - M. Zulfikri Febriansyah; Eja Armaz Hardi; Rabiyatul Alawiyah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
BUMDes is a pillar of economic activity in the village which functions as a social and commercial institution. BUMDes as a social institution supports the interests of the community through its contribution in providing social services. Meanwhile, as a commercial institution, its aim is to seek profits by offering local resources (goods and services) to the market. The aim of this research is to determine the effectiveness and efficiency of financial management in Village-Owned Enterprises (BUMDes) in Lubuk Lawas Village, Batang Asam District and to determine the optimization of village fund management by Village-Owned Enterprises (BUMDes) in Lubuk Lawas Village in influencing growth. sustainable local economy. The research method uses a qualitative approach. Data collection techniques use observation, interviews and documentation. The research results show that the main step taken to realize this goal is to socialize and provide training to the community. To maintain transparency, accountability and effectiveness in the management of BUMDes in Lubuk Lawas Village, monitoring is carried out by monitoring the success of the program and the budget. However, the lack of village community participation means that the reach of the BUMDes program is still uneven in improving the economic welfare of the people of Lubuk Lawas Village. Efficiency Measuring the efficiency of BUMDes in Lubuk Lawas Village can be seen from the number of people involved in BUMDes business units, the number of business units available and the performance of BUMDes in improving the economic welfare of the people of Lubuk Lawas Village. However, the uneven distribution of programs and benefits felt by the community means that the BUMDes program can be said to be still inefficient. The management of village funds by Village-Owned Enterprises (BUMDes) in Lubuk Lawas Village in influencing sustainable local economic growth is still not optimal.